The Prognostic Impact of Smoking Status, Cessation, and Anticoagulation-Interaction on Adverse Outcomes in Patients with Atrial Fibrillation: A Systematic Review - Siti Tari Salsa (International Medical Journal Corp. Ltd, 2025)
Introduction: Atrial fibrillation (AF) and tobacco smoking represent two of the most significant and concurrent global health burdens. While smoking is an established risk factor for the development of incident AF, its prognostic impact following an AF diagnosis has remained controversial, particularly regarding thromboembolic risk (Zhu, Guo, & Hong, 2016). This systematic review synthesizes the evidence on the association between smoking status (current, former, and cessation) and a comprehensive range of adverse outcomes in patients with established AF. Methods: A systematic review was conducted adhering to PRISMA guidelines. The Cochrane Library, PubMed, and Embase databases were searched for observational studies (cohort or case-control) and meta-analyses evaluating the prognostic impact of smoking in patients with a confirmed AF diagnosis. Methodological quality and risk of bias for all included non-randomized studies were rigorously assessed using the 9-star Newcastle-Ottawa Scale (NOS) (Wells et al., 2000). Results: A total of 17 high-quality observational studies, including large national cohorts and one key meta-analysis, were included. The evidence was consistent and significant that persistent smoking is associated with increased all-cause mortality (Relative Risk 1.82, 95% CI 1.33–2.49) (Zhu, Guo, & Hong, 2016) and cardiovascular death (RR 1.54, 95% CI 1.31–1.81) (Zhu, Guo, & Hong, 2016). Smoking was also a significant predictor of major bleeding (RR 1.93, 95% CI 1.08–3.47) (Zhu, Guo, & Hong, 2016) and AF recurrence post-catheter ablation (RR 3.19, 95% CI 1.23–8.27) (Okutucu et al., 2010). The association with stroke was contradictory (the